Capital Budgeting Analysis, Sensitivity Analysis, and Monte Carlo Simulator for Mbah Jingkrak's New Outlet - Maharani, Nadia Putri; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2015)
Abstract.This research was conducted in order to assess the expansion plan of Mbah Jingkrak, a Javanese traditional restaurant located, that is going to build new outlet in Serpong, South Tangerang. The objective of this research is to make sure that the investment will give positive financial outcome to the company. In order to give clear projection of its financial performance, 3 steps of study are conducted, which are feasibility study for capital budgeting assessment, sensitivity analysis, and Monte Carlo Simulation. The results of feasibility study shows that the NPV of the project is positive, the internal rate of return exceed the projectÃ¢â‚¬â„¢s cost of capital, and there are no indications of negative cash flow, which show that the project of the expansion plan is financially feasible and viable. On the next step, which is sensitivity analysis, the project shows that the 4 most sensitive factors are: the cost of raw materials, the first year occupancy, spending per customer, and the growth of restaurantÃ¢â‚¬â„¢s occupancy. These 4 most sensitive factors need to have higher attention from management since these factors have the lowest tolerance scale and need to be kept as close as possible to the assumptions in order to maintain positive financial outcome. Lastly, under Monte Carlo Simulation, the project shows a promising result, where the probability of expecting positive Net Present Value is above 85,90%, supported with only 3,80% probability of cash shortage. These indicators lead to a conclusion that the restaurantÃ¢â‚¬â„¢s plan to open new outlet should be executed. Using these conclusions, Mbah Jingkrak can design implementation plan for its new outlet. The implementation of these results includes setting sales and cost target, complemented with menu combination and innovation to increase customerÃ¢â‚¬â„¢s spending and restaurantÃ¢â‚¬â„¢s occupancy.Keywords : Capital Budgeting, Feasibility Study, Sensitivity Analysis, Monte Carlo Simulation.Ã‚Â